Breaking the Linguistic Minority Complex through Creative Writing and Self-Translation - Dagnino, Arianna (TTR)

(untitled) (Association canadienne de traductologie, 2019)
Generally speaking, a minority language is “one spoken by less than 50 percent of a population in a given region, state or country” (Grenoble and Singerman, 2017, n.p.). In this article, I propose a more contextualized definition that applies to the realm of literary writing and (self-)translation. Thus, I define a minority language as any language which a bilingual or plurilingual writer perceives as not being the dominant one in the sociocultural and linguistic context in which s/he is active as an author or as a (self-)translator. Assuming this alternative definition as a point of departure, I discuss the creative and self-translational practice of the Canadian writer Antonio D’Alfonso. D’Alfonso is one of those rare plurilingual writers who feel linguistically defamiliarized, claiming that instead of having a proper mother tongue he has a mixed baggage of native Molisano dialect, French, English and Italian. Thus, he tends to write, think and (self-)translate immersed in a kind of 3D- (or even 4D-) linguistic landscape (Pivato, 2002). D’Alfonso’s self-translations from French into English and/or vice versa are testimony to the author’s experimental way of challenging the “crude subjugation” (Whyte, 2002, p. 69) of a language over another and of overcoming any minority-language complex he might have developed on his path to becoming a linguistically uprooted writer.